An overview of regulatory approaches to genome editing in agriculture. Issue 2 (July 2019) - Friedrichs, Steffi; Takasu, Yoko; Kearns, Peter; Dagallier, Bertrand; Oshima, Ryudai; Schofield, Janet; Moreddu, Catherine
Abstract: The " OECD Conference on Genome Editing: Applications in Agriculture – Implications for Health, Environment and Regulation ", brought together policy makers, academia, innovators and other stakeholders involved in the topic, in order to take stock of the existing research and applications of genome editing, and to thereby provide science-based input to the discussion of the potential impact of genome editing in the context of overarching agricultural and food policies. The conference provided a timely opportunity for information exchange between scientific experts, risk assessors, policy makers, regulators, private sector innovators and other stakeholders from around the world. In this paper, we summarise the conference session on the "Regulatory aspects" concerning genome editing ( Session 3 ), during which government representatives from six different countries around the world reported on the policy frameworks pertaining to genome editing in their respective countries, and discussed their specificities, as well as the common issues encountered.